Pectolytic enzyme activities of some foliar fungi isolated from mangrove plants and their response to tannin - R.P. PURKAYASTHA, R. PURKAIT and (Indian Phytopathology, 2002)
Foliar fungi isolated from mangrove plants of the Sundarbans, West Bengal, India, were tested for their pectolytic enzyme activity and growth response to tannin. Of the 15 fungi tested, Colletotrichum gloeosporioides [Glomerella cingulata] and Coniella musaiaensis showed max. and min. enzyme activities, respectively, under identical conditions. Tannin (0.2%) inactivated the pectolytic enzymes of all fungi but most significantly those of Phoma nebulosa. Pestalotiopsis sp. and Myrothecium cinctum were the least and the most sensitive to tannin, respectively. There was no correlation between growth and enzyme activity or between tannin sensitivity and enzyme activity. However, an apparent correlation was noted between high tannin sensitivity and lowenzyme activity of 5 fungi.